“Apa yang Siswa Pikirkan Tentang Matematika?” Analisis Sentimen pada Siswa Kelas Tinggi Sekolah Dasar - Widyastuti, Widyastuti; Dasari, Dadan; Noer, Sri Hastuti (Faculty of Teacher Training and Education, 2024)
The purpose of this study was to describe a sentiment model for elementary school students' comments on mathematics. Respondents in this study were 286 elementary school students in seven elementary schools in Bandar Lampung. Sentiment data were obtained through student comments that were collected in May-June 2024. Data analysis used sentiment analysis and mood analysis based on student comment texts carried out using Ekman's Basic Emotions classification. The analysis was carried out through Orange software using Corpus analysis, sentiment analysis, topic modeling, and also tweet profiler. The results of the analysis revealed that: i) the sentiment of elementary school students was dominated by positive sentiment (percentage achievement of 50%), with the three most keywords expressed in students' textual comments about mathematics were